KARAKTERISTIK GEOMORFOLOGI GUNUNG API AKTIF DAN GUNUNG API PADAM: KASUS G. MERAPI & G. GAJAHMUNGKUR, DAERAH ISTIMEWA YOGYAKARTA DAN JAWA TENGAH - Hartono, Hill G.; Sudradjat, Adjat (Bulletin of Scientific Contribution, 2018)
The volcanic morphology provides the information about the history of the genesis and activities of an active volcano which is still developing as demonstrated by Merapi strato volcano in Special Provinve of Yogyakarta and Central Java. The purpose of the present study is to reveal the history of the geomorphology of the dormant volcano (such as Gajahmungkur volcano, Wonogiri) based on the comparative study of the active volcano (Merapi volcano, Yogyakarta). The method in this study is the application of geological principle “the present is the key to the past” in the geology of a volcano. In general the volcanological facies concept reflects the ideal morphology of Merapi volcano. The central facies with the slope of 300 to 400 and the smooth surface; medial facies with the slope of 200 to 300 reflecting rough surface and the distal facies manifested in a relatively flat angle between 100 to 200 where the deposition of volcanic materials and lahar takes place. The boundary between the facies is delineated by a break in slope which also reflects the radial drainage pattern and the boundary of vegetation